(untitled) (Research, Society and Development, 2024)
Medicinal plants, fundamental in the history and culture of peoples, have been used since ancient times for the treatment of diseases. The implementation of nurseries, such as the one at the Instituto Tecnológico Superior de Comalcalco (ITSC), not only promotes the conservation of these species, but also educates new generations about the importance of biodiversity and environmental sustainability. This study aims to describe the implementation of a medicinal plant nursery at ITSC and to classify the cultivated species according to their biological and propagation characteristics. A suitable site was selected within ITSC, materials for construction were collected, the nursery area was delimited, and the structure was built using sustainable methods. Native medicinal plants were collected, compost was made, and reproduction and propagation were carried out using various methods. Plants were classified according to their adaptation to local conditions and labeled for precise identification. A survey was conducted to assess the community’s knowledge and perception of the nursery. The implementation of the nursery at ITSC resulted in the classification of 37 medicinal plant species, highlighting families such as Lamiaceae and Asteraceae. The ITSC community showed a high knowledge and appreciation of medicinal plants, with 99.3% considering their conservation important. The best-known plants were basil and oregano, traditionally used for their medicinal properties. The implementation of the medicinal plant nursery at ITSC represents an effective strategy for the conservation and propagation of local medicinal species. This project not only promotes biodiversity and environmental education, but also strengthens cultural identity and traditional knowledge about the use of medicinal plants. Integrating these resources into the educational community fosters a holistic approach to health and environmental sustainability, thus contributing to more responsible and ecological practices.